Metabolic syndrome, insulin resistance, fibrinogen, homocysteine, leptin, and C-reactive protein in obese patients with obstructive sleep apnea syndrome - Basoglu, Ozen K. (Medknow Publications, 2011)
OBJECTIVE: The prevalence of obstructive sleep apnea syndrome (OSAS) and metabolic syndrome is increasing worldwide, in part linked to epidemic of obesity. The purposes of this study were to establish the rate of metabolic syndrome and to compare fibrinogen, homocysteine, high-sensitivity C-reactive protein (hsCRP), leptin levels, and homeostasis model assessment insulin resistance (HOMA-IR) in the obese patients with and without OSAS. METHODS: The study population included 36 consecutive obese patients with OSAS (23 males; mean age, 50.0 ±19.7 years), and 34 obese patients without OSAS (17 males; mean age, 49.7±11.1 years) were enrolled as control group. Metabolic syndrome was investigated; fibrinogen, homocysteine, CRP, and leptin levels were measured, and IR was assessed. RESULTS: Metabolic syndrome was found in 17 (47.2%) obese OSAS patients, whereas only 29.4% of obese subjects had metabolic syndrome (P > 0.05). Obese patients with OSAS had significantly higher mean levels of triglyceride (P < 0.001), total-cholesterol (P = 0.003), low-density lipoprotein-cholesterol (P = 0.001), fasting glucose (P = 0.01), HOMA-IR (P <0.001), thyroid-stimulating hormone (P = 0.03), fibrinogen (P < 0.003), hsCRP (P <0.001), and leptin (P = 0.03) than control group . Besides, leptin level was positively correlated with waist (r = 0.512, P = 0.03) and neck circumferences (r = 0.547, P = 0.03), and fasting glucose (r = 0.471, P = 0.04) in OSAS patients, but not in obese subjects. CONCLUSION: This study demonstrated that obese OSAS patients may have an increased rate of metabolic syndrome and higher levels of serum lipids, fasting glucose, IR, leptin, fibrinogen, and hsCRP than obese subjects without sleep apnea. Thus, clinicians should be encouraged to systematically evaluate the presence of metabolic abnormalities in OSAS and vice versa.